Weekly reciprocal relationships between job crafting, work engagement, and performance—a within-person approach - Lopper, Elisa; Milius, Marvin; Reis, Dorota; Nitz, Sandra; Hoppe, Annekatrin (Frontiers in Organizational Psychology, 2023)
Introduction Following the principles of the conservation of resources theory, this study explored whether job crafting, work engagement, and performance are reciprocally related from one week to the next. Method Data (N = 175) from a weekly diary study were analyzed using a random intercept cross-lagged panel model (RI-CLPM) to differentiate between stable trait-like between-unit and state-like within-person components. Results The results revealed that, within weeks, job crafting, work engagement, and performance are associated with each other. Across weeks, on average, job crafting levels predicted work engagement and performance at the within-person level the following week. Inversely, work engagement, on average, predicted job crafting the next week, providing evidence for a positive cycle between both variables. Finally, work engagement and performance were reciprocally related from one week to the next, although the effects varied significantly in magnitude and direction. Discussion Overall, the within-person relationships between job crafting, work engagement, and performance were more heterogeneous than anticipated.